The War scroll, violence, war and peace in the Dead Sea scrolls and related literature : essays in honour of Martin G. Abegg on the occasion of his 65th birthday - Abegg, Martin G.; Davis, Kipp.; Baek, Kyung S.; Flint, Peter W.; Peters, Dorothy M., 1958- (Studies on the Texts of the Desert of Judah, 2015)
This volume is a collection of essays written in honour of Martin G. Abegg from a range of contributors with expertise in Second Temple Jewish literature in reflection upon Prof. Abegg's work. These essays are arranged according to four topics that deal with various aspects of text, language and interpretation of the Qumran War Scroll , and concepts of war and peace in Second Temple Jewish literature. The contents of the volume are divided into the following four main sections: (1) The War Scroll , (2) War and Peace in the Hebrew Scriptures, (3) War and Peace in the Dead Sea Scrolls, and (4) War and Peace in early Jewish and Christian texts and interpretation.